1997
DOI: 10.1016/s0960-9822(06)00119-9
|View full text |Cite
|
Sign up to set email alerts
|

The folding catalyst protein disulfide isomerase is constructed of active and inactive thioredoxin modules

Abstract: Our determination of the global fold of the b domain of PDI by NMR reveals that, like the a domain, the b domain contains the thioredoxin motif, even though the b domain has no significant amino-acid sequence similarities to any members of the thioredoxin family. This observation, together with indications that the b' domain adopts a similar fold, suggests that PDI consists of active and inactive thioredoxin modules. These modules may have been adapted during evolution to provide PDI with its complete spectrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
193
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 208 publications
(199 citation statements)
references
References 42 publications
5
193
0
1
Order By: Relevance
“…The groups of Creighton [9] and So$ ling [10] have recently shown that PDI is composed of four thioredoxin domains, and not two as was previously believed. The model of the domain structure of PDI, as shown in Figure 2, is based on our previous work [10] and has been adjusted for and combined with the structural data supplied for the b domain [9] and extended to accommodate all domains and all members of the family (see Figure 3).…”
Section: Pdi Modelmentioning
confidence: 83%
See 4 more Smart Citations
“…The groups of Creighton [9] and So$ ling [10] have recently shown that PDI is composed of four thioredoxin domains, and not two as was previously believed. The model of the domain structure of PDI, as shown in Figure 2, is based on our previous work [10] and has been adjusted for and combined with the structural data supplied for the b domain [9] and extended to accommodate all domains and all members of the family (see Figure 3).…”
Section: Pdi Modelmentioning
confidence: 83%
“…Its structure encompasses two double-cysteine, redox-active sites, each within domains with high sequence similarity to thioredoxin [7,8], separated by a further two thioredoxin-related domains (hereafter referred to as thioredoxin fold domains) lacking reactive cysteines [9,10]. It is a highly abundant ER luminal including peptide binding, cell adhesion and perhaps chaperone activities.…”
Section: Pdimentioning
confidence: 99%
See 3 more Smart Citations